(untitled) (Global Journal of Science Frontier Research, 2020)
The reactions of chlorazone with α-chloroethyl esters of n-C 8 H 17 OH, n-C 10 H 21 OH, n-C 12 H 25 OH, CH 3 -CH=CCl-CH 2 OH alcohols for the first time were carried out, and chlorazone esters containing two ROCH 2 groups of these esters were obtained. The reactions of N 1 -alkoxymethyl-N 3 -alkoxymethylguanidine compounds with these chlorazone esters were carried out and 4 new guanidine derivatives (conventionally designated as I-IV) were synthesized, not known in the literature. Studies have been conducted to establish corrosion inhibitory efficiency for each of the newly synthesized compounds of guanidine I-IV in a very strong aggressive environment created in the laboratory. It was established that the inhibitory effectiveness of these compounds in concentrations of 1.0; 2.0; 2.5 mg/l is 99.97-100%. A comparative study of the effective inhibitory properties of the new synthesized guanidine compounds for corrosion protection of steel "St.3" was carried out. Studies have shown that each of the new I-IV compounds of guanidine in terms of environmental safety, economic and environmental efficiency is 5-10 times higher than the inhibitors currently used to protect from corrosion steel processing equipment operating in aggressive environments.